The development of a microtakaful model to serve the underprivileged: low income and the poor in selected states in Malaysia / Noorashikin Mohd Rom - Mohd Rom, Noorashikin (2014)
Microtakaful is one of the mechanisms to alleviate the poverty and to provide necessary protection to low income and the poor. The purpose of this research is to investigate the need for protection (microtakaful) among low income and the poor respondents and finally to develop a suitable microtakaful model based on the findings of the survey, theories and literature reviews. Firstly, need for protection was examined by investigating respondents' demographic profile, their exposure to risks, vulnerability (coping strategies), their financial literacy (ability to save and indebtedness), the awareness level, their capacity to contribute, attitude and trust towards takaful or insurance. Secondly, a new variable namely capacity to contribute was established to investigate the statistical relationship with the need for protection. Thirdly, this study employed income and education level as moderators to moderate vulnerabilities and need for protection. The objective is to find the moderation effect of income and education level on vulnerabilities and need for protection. Another new moderator namely government role is employed to test the relationship between capacity to contribute and need for protection. Fourth, this study also investigates respondents' protection and contribution method preferences, mode of contribution and finally an affordable amount that they are willing to part with on a monthly basis. Need for protection would reflect the potential demand for these population; low income and poor. A face-to-face survey via 760 questionnaires from low income and poor group with household monthly income ofRM2,000 and below has been conducted in Kedah, Kelantan and Terengganu. Data was collected and subsequently analyzed to gauge on how microtakaful will be able to assist them in uplifting their economic status. A Structural Equation Modeling (SEM) technique by using AMOS 20.0 software is applied to this research. Six hypotheses namely risks exposure (HI), vulnerability (H₂) , awareness level (H₃) , attitude and trust (H₄) , ability to save (H₅) and capacity to contribute (H₆) on the relationship with need for protection were examined. Another three hypotheses namely income level (H₇) , educational level (H₈) and government role (H₉) were examined under moderation effect. Results indicated that five hypotheses (H₁, H₂, H₃, H₅, and H₆) out of six hypotheses are statistically significant. However, hypothesis H4 (attitude and trust) was rejected because it was not found to be significant in the hypothesized direction. Hypotheses of income level (H₇), education level (H₈) and government role (H₉) found to be statistically significant and have moderating effects. The eventual Microtakaful Model is proposed at the end of this research will include government role and relevant mechanisms that will be specially designed for the Malaysian low income and poor. A model will assist takaful operators and the government in serving this niche population. By establishing the model, optimistically low income and poor could have their own microtakaful scheme which should be able to provide sufficient benefits thus preventing them from being trapped in the poverty cycle permanently. Nevertheless, the intervention and support from government is vital in providing the financial capacity for low income and poor to have the needed protection.